Pola asuh dan pola makan sebagai faktor risiko stunting balita usia 6-24 bulan suku Papua dan non Papua di wilayah kerja Puskesmas Arso III kabupaten Keerom - Fiyanita Nesa Ramadhani; BJ Istiti Kandarina; I Made Alit Gunawan (Berita Kedokteran Masyarakat (BKM), 2019)
Parenting and feeding paterns as risk factors for stunting toddlers aged 6-24 months Papuans and Non-PapuansPurpose: Stunting or short is one indicator of chronic nutritional status that has long-term effects. The stunting prevalence in Indonesia in 2013 was 37.2% and in Papua in 2016 amounted to 51.72%. In 2017 there were 527 stunting toddlers in Keerom Regency and 214 toddlers found in Skanto District. This study aims to determine the risk of parenting and feeding patterns to the incidence of stunting of children aged 6-24 months in the Papuan and Non-Papuan tribes in the Arso III Health Center, Keerom. Method: This type of research is observational with a case-control design. A total of 160 toddlers were divided into 40 cases and 40 controls in each tribe. Data collection uses parenting questionnaires and SQ-FFQ. Data analysis used the Independent T-Test, Mann-Whitney, Chi-Square and Multiple Logistic Regression. Results: The results of the bivariate analysis showed that there were differences in energy and protein intake and there were no differences in parenting and types of food in Papua and non-Papuan stunting children. In the Papuan tribe there is a relationship between parenting (OR=5.57), energy intake (OR=16.71), protein intake (OR=13.77), type of food (OR=4.63), and incidence of diarrhea (OR= 3.14) with the incidence of stunting. In the Non-Papuan tribe, there is a relationship between parenting (OR=8.03), energy intake (OR=11.76) and protein intake (OR=26.71) with the incidence of stunting. The results of multivariate analysis showed that the factors that contributed to the incidence of stunting in the Papuan tribe were parenting, energy intake, protein intake, and diarrhea, while in the Non-Papuan tribes were parenting, energy intake and protein intake. Conclusion: Parenting, energy intake and protein intake are risk factors for stunting in Papuans and non-Papuans. Energy intake is the most dominant factor in Papuans, while in Non-Papuans is protein intake. It is hoped that the local government can create special family assistance programs or activities to overcome stunting and use land that can prevent or overcome stunting.